2020
DOI: 10.3389/fmicb.2020.01644
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel katG Mutations Conferring Isoniazid Resistance in Mycobacterium tuberculosis

Abstract: Tuberculosis (TB), an infectious disease caused by Mycobacterium tuberculosis, is among the top 10 leading causes of death worldwide. The treatment course for TB is challenging; it requires antibiotic administration for at least 6 months, and bacterial drug resistance makes treatment even more difficult. Understanding the mechanisms of resistance is important for improving treatment. To investigate new mechanisms of isoniazid (INH) resistance, we obtained three INH-resistant (INH-R) M. tuberculosis clinical is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The higher number of positive samples are shown by the group of people that suffering from the symptoms for 20 months (6 samples), followed by those who were suffering for 21 months (4 samples), then 19 months (3 samples), then the infection periods 17 and 12 showed 2 samples, and the infection periods 15, 11, and 8 showed only one sample. The results of isolates resistance to Rifampicin and Isoniazid in tabular form (6). The findings revealed that seven percent the positive samples are resistance to Rifampicin and (4%) were sensitive.…”
Section: Figure 1: Amplification Curves Of M Tuberculosis Results Of ...mentioning
confidence: 95%
See 1 more Smart Citation
“…The higher number of positive samples are shown by the group of people that suffering from the symptoms for 20 months (6 samples), followed by those who were suffering for 21 months (4 samples), then 19 months (3 samples), then the infection periods 17 and 12 showed 2 samples, and the infection periods 15, 11, and 8 showed only one sample. The results of isolates resistance to Rifampicin and Isoniazid in tabular form (6). The findings revealed that seven percent the positive samples are resistance to Rifampicin and (4%) were sensitive.…”
Section: Figure 1: Amplification Curves Of M Tuberculosis Results Of ...mentioning
confidence: 95%
“…The majority of Mutations in the katG gene, the inhA gene and its promoter, or the oxyR-ahpC region, all of which are involved in cell wall synthesis, confer INH resistance (INH-R) to strains (Hsu et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…3,34,37 However, Current research has shown that resistance to isoniazid can also be caused by an upregulation of efflux pumps or isoniazid inactivators. 38,39 Mutations in the katG, inhA and its promoter, and the oxyR-ahpC intergenic region frequently confer resistance to INH. 3,22,29 While mutations in the following genes oxyR, furA, ndh, ahpC, kasA, and fabG1-inhA infrequently confer resistance to INH.…”
Section: Drug Target Genes and Mutations Conferring Resistance To Iso...mentioning
confidence: 99%
“…The H37Rv gyrA D94K is a M. tuberculosis strain resistant to moxifloxacin, which contains a mutation of gyrA (D94K) that encodes DNA gyrase subunits and was identified as the most common mechanism to result in fluoroquinolone-resistant tuberculosis [43]. H37Rv katG del is an isoniazid mono-resistant strain containing a catalase-peroxidase (katG) gene mutant associated with cell wall synthesis [44]. The active compounds demonstrated similar activity against the mono-resistant strains (rpoB S450L or gyrA D94K or katG del ).…”
Section: Machine Learning Antitubercular Activity and Compound-drug Similarity Predictionmentioning
confidence: 99%